Penyuluhan Manfaat Aromaterapi Lavender dalam Persiapan Persalinan bagi Ibu Hamil di Desa Padangsambian Kaja Denpasar Barat Bali - Noviani, Ni Wayan; Praminingrum, I. G. A Raras (Jurnal Pengabdian UNDIKMA, 2022)
This service aims to provide counseling to pregnant women in the third trimester about the benefits of lavender aromatherapy in preparation for childbirth. The Kartini Health Polytechnic in Bali reaches out to Dwijendra University Denpasar and Puskesmas I Denpasar Barat which covers the Padangsambian Kaja Village as a target village, organizes Posyandu activities every month and one of the programs is for pregnant women. The method used in this service is direct counseling by implementing health protocols during the Covid-19 pandemic. Participants in this service program are third trimester pregnant women. The results of the outreach activities have helped pregnant women to prepare for a comfortable and safe delivery with the help of media in the form of leaflets and posters. The evaluation of the implementation of this community service was an increase in knowledge about the benefits of lavender aromatherapy and a positive response seen from the score of the satisfaction evaluation results, namely 80% expressed satisfaction with this activity.